Carrry' Subtype of Motion Verbs in English and Buginese - Reza Apreliah Dg Matara (Tolis Ilmiah: Jurnal Penelitian, 2019)
The aims of this research were (1) to identify the motion verbs in English and Buginese based on the “Carry” subtype. (2) to investigate the similarities and differences of motion verbs of ’Carry’ subtype in English and Buginese. The data of this research consists of English and Buginese. English data were collected from Corpus of Contemporary American English (COCA), while data of Buginese were obtained from field research through the process of observation, and in-depth interview. Both of the data were analyzed by using a descriptive and qualitative method. The result of this research reveals that (1) There are four motion verbs of ‘Carry’ subtype in English, they are carrying, bear, cart and transport. In Buginese there are twelve motion verbs found in this research, they are mattiwi, massoppo, majjujung, maddenge, mangepa, makkaleppi, matteteng, mabbiccang, marrenreng, mallempa, matteke and maggandeng. (2) From clause structure, it can be found that the clause structure in Buginese has some variations. In Buginese there are two prepositions that have a similar meaning and different usage, they are ri and ku which mean in.